Digital photography : the missing manual - Grover, Chris (Missing manual., 2006)
Digital Photography: The Missing Manual helps you to take beautiful digital pictures -- of your baby, your trip to Paris, your new pet iguana--and then share the stunning results with your friends and family. Spiked with the advice and humor that are trademarks of the Missing Manual series, this book shows you how to: Master your digital camera. Learn how to use those mysterious buttons and modes to improve your pictures. Take memorable photographs Become a better photographer right away with a few simple tricks from the pros. Edit your photos to remove red eye, or crop out extraneous buildings. Add colors and effects not normally found in nature. Share your pictures using the best programs and Web sites for sharing your photos-in print, online, and via ESP. This is a great book for people who want to get started with digital photography but it's also perfect for those who need to increase the skills they already have. Intermediate digital photographers will love the tips and tricks from the pros and the helpful buying guides for those accessories they're ready to add. Note: This book is Windows-only. For Mac fans, iPhoto 6: The Missing Manual has a whole section on digital photography.